Surgical Pathology of Hepatobiliary Tumors - Cong, Wen-Ming (Springer Singapore : Imprint: Springer, 2017)
This book focuses on the pathological diagnosis of primary hepatic and bile duct tumors, and introduces the "Three Types and Six Sub-types" classification of hepatobiliary tumors. With more than 600 figures, including photographs and microscopy images, it highlights morphology, immunology and molecular pathology and their correlations with hepatic surgery and hepatic oncology. The book reviews the pathobiological characteristics of hepatic tumors and reveals the latest developments in this field. It is a valuable reference resource for hepatologists, pathologists and researchers.
Keywords: Medicine.; Hepatology.; Oncology.; Pathology.; elektronické knihy; electronic books